STUDIES ON RESIN PURIFICATION PROCESS OPTIMIZATION OF EUCOMMIA ULMOIDES OLIVER AND ITS ANTIHYPERTENSIVE EFFECT MECHANISM - Yongsheng, Liu; Shumei, Li; guodong, Wu (African Journal of Traditional, Complementary and Alternative Medicines, 2014)
Background: Through research it is found that the barks, Oliver, stems, fruits and flowers of Eucommia ulmoides contain various compositions, such as lignin, cycloalkane and phenylpropanoids. The modern pharmacological research shows that Eucommia ulmoides has many functions, such as anti-aging, antitumor and bone cell proliferation. This paper studies the resin purification process optimization conditions and antihypertensive effect of Eucommia ulmoides Oliver. Materials and Methods: The orthogonal experiment method is adopted to determine the purification effect of various macroporous resin for eucommia ulmoides Oliver, and the SHR model is used to determine antihypertensive level of eucommia ulmoides Oliver. Results: The optimal process of resin extraction and purification of Eucommia ulmoides Oliver is that the loading liquid concentration is 6 mg/ml, 20% ethanol is used as the eluent, the flow rate control is 3.0 column volume per hour and the diameter-height ratio of adsorption column is 1:6; the extracts of Eucommia ulmoides Oliver can reduce SHR blood pressure, its antihypertensive effect is relatively stable and has no significant impact on HR, but the antihypertensive effect is lower than that of control medicine captopril. At the same time, the extracts of eucommia ulmoides Oliver can significantly increase the content of serum NO and reduce the content of ET. Conclusion: the Eucommia ulmoides Oliver can relax blood vessels, reduce the peripheral resistance, reduce the returned blood volume, and eventually achieve the antihypertensive effect.